First description of the male Hoedillus sexpunctatus Simon, 1898; a redescription of the female, and transfer of Hoedillus to Zoropsidae Bertkau, 1882 (Araneae) - Leister, Matthew; Miller, Kelly B. (Zootaxa, 2016)
Hoedillus sexpunctatus Simon, 1898 was described from a single female specimen collected in Guatemala and is the type species of the monotypic genus Hoedillus Simon, 1898. This genus was originally placed in the family Sparassidae Bertkau, 1872, subfamily Heteropodinae Thorell, 1873. In a review of this subfamily, Jäger (2002) determined that Hoedillus was misplaced in Sparassidae due to the lack of metatarsal trilobate membranes. Hoedillus was transferred to the family Zoridae Pickard-Cambridge, 1893 by Jäger (2002), now a junior synonym of Miturgidae Simon, 1886 (Ramírez 2014). Ramírez (2014), suggested Hoedillus may be a member of the Xenoctenus group, but provisionally listed it as a Miturgidae, awaiting further investigation.